Sports psychology concepts and applications - Mangal, S. K.; Mangal, Shubhra (Routledge, 2024)
"This book analyses the essential psychological aspects of sports psychology by throwing light on issues related to upkeep of the athletes' mental state and improving their performances in the sports activities. On one hand, it covers topics like anxiety, stress, conflicts, overtraining, and sports injuries and on the other hand it includes strategies helpful for managing and developing skills for better performance in various sports activities. In its wide coverage, the volume discusses a range of key topics which include sports Psychology-Historical perspectives and the present position; contribution of heredity and environment, the role of growth and development, and the individual differences in sports psychology; how factors like intelligence, cognitive and emotional processes, personality, and motivation influence learning and transfer of learning? ; the role of attention, concentration and focus in the performance of athletes; athletes' mental and psyche level displayed in the states of their anxiety, stress and conflicts, aggression and violence; sports injuries and their management; group dynamics and guidance & counselling in the learning and development of the athletes, etc. Engaging and reader-friendly, this book will be useful to the students, researchers and teachers of physical education, psychology, applied psychology, and sports psychology. It will also be key reading for trainees of the various sport academies, coaches, sports associations, managing bodies, and sport psychologists"--